2020
DOI: 10.1002/pst.2028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two treatments in the presence of competing risks

Abstract: Summary Competing risks data arise frequently in clinical trials, and a common problem encountered is the overall homogeneity between two groups. In competing risks analysis, when the proportional subdistribution hazard assumption is violated or two cumulative incidence function (CIF) curves cross; currently, the most commonly used testing methods, for example, the Gray test and the Pepe and Mori test, may lead to a significant loss of statistical testing power. In this article, we propose a testing method bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…ρ is difficult to estimate because it involves the assumption of an unknown underlying CIF distribution of the actual data. Lyu et al[20] found that when 0.50…”
mentioning
confidence: 99%
“…ρ is difficult to estimate because it involves the assumption of an unknown underlying CIF distribution of the actual data. Lyu et al[20] found that when 0.50…”
mentioning
confidence: 99%